PENGARUH METODE SPEED READING BERBASIS DIGITAL TERHADAP KEMAMPUAN MEMBACA SISWA MATA PELAJARAN BAHASA INDONESIA KELAS II SDN KEPUH KIRIMAN 1 WARU - Ahmad Alwan Nafis; Rarasaning Satianingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Speed ​​Reading method is considered an effective approach to improve students' reading comprehension. This method uses special techniques to increase students' reading speed without reducing their understanding of the text. In today's digital era, The use of technology is increasingly widespread in various fields of life, including education. This study was conducted with the aim of determining whether the digital-based speed reading method has an effect on the reading ability of Indonesian language students of grade 2 SDN Kepuh Kiriman 1 Waru. This study is a quantitative study. The design used is nonequivalent control group design, which is a type of quasi-experimental design with a post-test control group design that is only carried out at SDN Kepuh Kiriman 1 Waru. This study used two groups, namely class II-A as the experimental group consisting of 26 students and class II-B as the control class consisting of 26 students. Information was collected through a student reading ability test. Based on the results of the analysis carried out through the normality test, homogeneity test and t-test, the results showed that the advanced speed reading method had a significant effect between the learning achievement scores of students in the experimental and control classes. Thus, it can be concluded that the speed reading method has an effect on the reading ability of Indonesian language students of grade II SDN Kepuh Kiriman 1 Waru.